Pengaruh Ekstrak Minyak Ikan Patin Terhadap Kadar Kolesterol Hdl Rattus Norvegicus yang Diinduksi Aloksan - TEO AL_ABDUL; FITRI HANDAJANI; TRI MARTINI SUMARNO (HANG TUAH MEDICAL JOURNAL, 2022)
Diabetes mellitus is a chronic condition due to insufficient amount of insulin produced by the pancreas. This condition can cause dyslipidemia. This study aimed to observe the effect of catfish (Pangasius sp) fish oil extract on HDL cholesterol level in male white rat (Rattus norvegicus) with alloxan-induced diabetes model. Alloxan was used to create diabetic conditions in the rats and the administration of catfish oil extract which contain omega-3 was expected to increase HDL cholesterol level. This is an experimental laboratory study carried out in the Biochemistry Laboratory Hang Tuah Medical Faculty from the beginning of May 2021 to the end of December 2021. Twenty seven male white rats selected based on the simple random sampling method divided into 3 groups: the negative control group with standard feeding and PDAM drinking water, the positive control group induced by alloxan 150 mg/kgBW, and the treatment group induced by alloxan 150 mg/kgBW and 3 days later given catfish (Pangasius sp) fish oil extract 73 mg/kgBW for 14 days. At the end of the study HDL cholesterol levels were measured in all sample. Data analysis showed lower HDL cholesterol levels in the positive control group (mean=20.78 mg/dl) than in the negative control group (mean=31.00 mg/dl) significantly (p = 0.004) and higher HDL cholesterol levels in the treatment group (mean=27.00 mg/dl) than in the positive control group (mean=20.78 mg/dl) athough the increase was not significant (p = 0.91). Conclusion of this study: the administration of catfish fish oil extract (Pangasius sp) dose of 73 mg/kgBW in alloxan induced male white rats (Rattus norvegicus) wistar strain increase HDL cholesterol levels although not significantly. Keywords : Pangasius sp, HDL Cholesterol level, Rattus norvegicus, Alloxan.